2013
DOI: 10.1155/2013/231434
|View full text |Cite
|
Sign up to set email alerts
|

Wind Tunnel Testing on Start/Unstart Characteristics of Finite Supersonic Biplane Wing

Abstract: This study describes the start/unstart characteristics of a finite and rectangular supersonic biplane wing. Two wing models were tested in wind tunnels with aspect ratios of 0.75 (model A) and 2.5 (model B). The models were composed of a Busemann biplane section. The tests were carried out using supersonic and transonic wind tunnels over a Mach number range of0.3≤M∞≤2.3with angles of attack of 0°, 2°, and 4°. The Schlieren system was used to observe the flow characteristics around the models. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The shock structure shown in Fig. 5 matches well with those reported in the literature for all range of Mach numbers [20].…”
Section: Grid Independence and Solver Validationsupporting
confidence: 85%
See 2 more Smart Citations
“…The shock structure shown in Fig. 5 matches well with those reported in the literature for all range of Mach numbers [20].…”
Section: Grid Independence and Solver Validationsupporting
confidence: 85%
“…The supersonic starting problem in three dimension differs significantly from that for a two dimensional Busemann biplane. The three dimensional biplane starts at a lower Mach number as compared to its two dimensional counterpart and the starting occurs at lower Mach numbers for smaller the aspect ratios of the biplane wing [20]. The elevation of starting problem occurs due the interaction of shock wave emanating from the winglets which chokes the flow [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the supersonic outlet condition (4b), the band (6) in which there exist asymmetric turbulent flows slightly expands:…”
Section: Asymmetric Flow At Zero Angle Of Attackmentioning
confidence: 99%
“…For a Busemann supersonic biplane, numerical simulations by Kusunose et al (4) and Hu et al (5) showed that the width of flow hysteresis under variations of the Mach number at the zero angle-of-attack is 0.54. Subsequent experiments revealed some discrepancy between the 2D simulations and tests for 3D biplane models which demonstrated the biplane start at lower Mach numbers, see Yamashita et al (6) .…”
Section: Introductionmentioning
confidence: 99%